A ANALISIS EFEKTIVITAS PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB P2) TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN DELI SERDANG - Clarayati Octavia Manalu; Wilda Sri Munawaroh Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2023)
This study aims to determine the effectiveness analysis of rural and urban land and building tax revenue (PBB P2) on local revenue (PAD) Deli Serdang district. This study emphasizes more on a process in solving problems with researchers directly involved in the object under study. The data collected can be in the form of interviews with informants which are described in a question, observation and literature study. The results of the data collection were analyzed and conclusions were drawn. So overall the level of effectiveness of PBB from 2017-2021 shows the criteria for an effective interpretation value, with an average percentage gain of 276%. And the data that has been obtained is known to the growth rate of PBB Kab. Deli Serdang. In 2021, the lowest PBB growth rate will only get a percentage of 71.15% with an interpretation value criterion that is effective.